Spatiotemporal analysis of snow cover variations at Mt. Kilimanjaro using multi-temporal Landsat images during 27 years. (June 2016) - Park, Sung-Hwan; Lee, Moung-Jin; Jung, Hyung-Sup
Abstract: The Landsat TM and ETM+ images have been acquired for the long period from the 1980s until the present with the temporal resolution of a 16-day repeat cycle from the visible, near infrared (NIR), short wave infrared (SWIR) and thermal infrared (TIR) bands. The Landsat multi-temporal images have been successfully used to monitor variations of the Earth surface during 27 years. In this paper, we observe the variations of (1) the snow cover area, (2) the snowline height and (3) the land surface temperature (LST) lapse rate at Mt. Kilimanjaro using a total number of 15 Landsat-5 TM and Landsat-7 ETM+ images from June 1984–July 2011. Segmentation of normalized difference snow index (NDSI) images with a threshold of 0.6 is used to extract snow cover. Snowline altitude is then determined by combining the snow cover classification maps with a digital elevation model (DEM). And the LST lapse rate is also calculated from the TIR band in the forest area. The results from this study show that (1) the snow cover area largely decreases from 10.1 km 2 to 2.3 km 2 during about 27 years, which corresponds to a 77.2% reduction, (2) the snowline height rose from 4760 m to 5020 m by about 260 m, and (3) the LST lapse rate shifted from −5.2 °C/km to −2.7 °C/km. This study demonstrates that multi-temporal Landsat images can be successfully used for the spatiotemporal analysis of long-term snow cover changes. Highlights: Spatiotemporal analysis of snow cover variations at Mt. Kilimanjaro using multi-temporal Landsat images during 27 years. Spatiotemporal analysis of snow cover variations at Mt. Kilimanjaro are performed. The snow cover variations are estimated from 18 Landsat images during about 27 years. The snowline height is changed from 4740 m to 5020 m by about 280 m for 27 years.